Murine matrix metalloproteinase 13 and its human homologue are involved in remodelling processes after myocardial infarction. (10th June 2022) - Braeuninger, H; Krueger, S; Becher, PM; Neumann, JT; Bacmeister, L; Voss, S; Warnke, S; Lang, V; Zeller, T; Laemmle, S; El-Armouche, A; Kirchhof, P; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): German Centre for Cardiovascular Research (DZHK) Background: Cardiovascular diseases such as myocardial infarction (MI) are a leading cause of death worldwide. Since matrix metalloproteinases (MMPs) are essential for the cleavage of collagen as well as for the modification of inflammatory proteins and cytokines, they play a substantial role in remodelling processes after MI. Purpose: Previous results of our group revealed, that Mmp13 expression is upregulated post-MI in mice, while it is downregulated after Ischemia/Reperfusion (I/R), indicating an involvement in remodelling processes. In humans, the functional homologue of Mmp13 is MMP1. Single nucleotide polymorphisms (SNPs) in the promotor of MMP1 can lead to alterations in its gene expression level. We analysed the genotype for 3 MMP1 SNPs in a human cohort containing 2000 patients who presented to the emergency department with suspected MI to identify their associations with development of MI and outcome after MI. Methods: The Mmp13 expression in different cardiac cell types was investigated at quiescent stage and under ischaemic conditions, to determine the cellular origin of Mmp13 expression. A MMP13-knockout (KO) mouse model was examined after induction of MI or I/R. Thus, gene expression analysis, histological staining and hemodynamic measurements were conducted to analyse differences between KO and WT as well as between MI and I/R. Out of the human cohort, 2 patient groups (non-MI and MI) were restricted, and Hazard ratios were calculated to evaluate risk for MI and risk for death after MI in dependency of the SNPs. Results: The Mmp13 expression in macrophages (6.6-fold to control; p=0.0286) and fibroblasts (4.9-fold; p=0.0079) increased significantly after activation with ischaemic secretome of cardiomyocytes, while Mmp13 expression of leucocytes was unaltered. After stimulation with ischaemic secretome of fibroblasts, Mmp13 expression in macrophages (4.3-fold; p=0.0286) and leukocytes (2.3-fold; p=0.0260) was significantly elevated as well. Comparing MI and I/R, the immune cell infiltration revealed significant differences 1-day post-intervention. About 50% of WT mice but only few KO mice died (p=0.0107) after MI due to cardiac rupture. Moreover, KO mice showed an improved cardiac function compared to WT mice after MI. Risk for death was significantly altered between the investigated genotypes in 2 of 3 investigated SNPs in the BACC cohort. Conclusion: Activated macrophages and leucocytes express high levels of Mmp13 in cell culture experiments. The infiltrating immune cell types are different between MI and I/R, which might lead to differences in Mmp13 expression in these models. MMP13 KO mice are protected from cardiac rupture after MI and unveiled improved cardiac function 28 days post-MI. SNPs of the human homologue of Mmp13 – MMP1 – showed an association of MMP1 with remodelling processes after MI.